A Multi-Faceted Analysis of Enablers and Barriers of Industrialised Building: Global Insights for the Australian Context - Sahar Soltani; Behzad Abbasnejad; Ning Gu; Rongrong Yu; Duncan Maxwell (Buildings)
This study examines the renewed interest in Industrialised Building (IB) adoption in Australia amid the housing crisis, addressing the gap between potential and implementation. Drawing on a systematic review of 171 peer-reviewed articles (1998–2024), we examine how the interplay between micro-level decision-making, meso-level organisational routines, and macro-level institutional arrangements shapes global IB adoption patterns, with implications for the Australian context where limited research exists. Our analysis highlights that successful IB adoption depends on coordinated alignment across systemic levels, with government policies and sustainability initiatives emerging as key global drivers. However, adoption barriers differ by market maturity; Australia faces unique challenges, such as economic constraints, limited stakeholder collaboration, and misaligned institutional frameworks, despite advancements in technology and innovation. The findings advance construction innovation literature by presenting a theoretically grounded framework to address IB adoption barriers and enablers. In the Australian context, realising IB’s potential requires co-evolution across micro, meso, and macro levels, driven by workforce upskilling, stakeholder collaboration, and adaptive regulations to transform construction practices.